The irony in the well-known poetry of Abdul Ghani Al-Rasafi and Fayez Peaks A comparative study - صباح كريم مولود (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Mockery is one of the most aesthetic literary arts produced by human thought, since it monitors the pulse of life with its pains and hopes through its fusion into the crucible of the reality where the artist finds his way. Therefore, mockery is a difficult technique as it depends on the manipulation of objects: exaggeration and magnification or understatement and degradation, and this manipulation is within a technical standard called the vindictive critical criticism in an atmosphere of humor and pleasure. Thus, this study is concerned with instances of mockery in the literature of Al-Rusafi and Peykes who are both Kurdish. While Al-Rusafi organized his poems in Arabic, Peykes organized his poetry in Kurdish. The significance of this study is that it deals with a subject that has not yet received due academic and scientific research, namely mockery in Peykes’ poetry. The researcher adopted the analytical descriptive method. The study falls into an introduction and two sections. The introduction part explores the concept of mockery in Arabic poetry, while the first section deals with the biography of the two poets, with a description of the similarities and differences between them. The second section tackles the types of mockery manipulated by the two poets. Three types are distinguished: social, religious, and political.